Mind games: Parental psychological control and emerging adults' adjustment. (February 2020) - Faherty, Amanda N.; Lowe, Katie; Arnett, Jeffrey Jensen
Although parental psychological control has been consistently linked with negative outcomes in the child and adolescent literature, little is known about how it functions during the developmental time frame of emerging adulthood, which is characterized by increased freedom and instability. Consequently, this study examined the extent to which paternal and maternal psychological controls were directly and indirectly (via self-esteem) related to hallmarks of emerging adult adjustment, notably risky behaviors, life satisfaction, and feelings about adulthood status. Recruited via MTurk, participants were 310 emerging adults ( M age = 25.37; 56% female) across the U.S. who completed an online survey. Results revealed paternal psychological control had a direct effect on risky behaviors and self-esteem, whereas maternal psychological control solely had a direct effect on risky behaviors. Results also indicated indirect effects of paternal psychological control. Increases in paternal psychological control were linked to declines in self-esteem, which in turn was associated with decreased life satisfaction and endorsement of adulthood status. Altogether, findings suggest that even low levels of parental psychological control were linked to detrimental outcomes in an age-representative sample—encompassing the full age range of emerging adulthood from 18 years to 29 years—of emerging adults. Thus, findings contribute to a better understanding of parent–child relationships and the consequences of parental control during the third decade of life, which has important implications for informing parenting strategies across emerging adulthood.